Food Safety & Environment – Mycotoxins and their impact on human health - Alvito, Paula (2019)
The National Institute of Health Dr. Ricardo Jorge (INSA) and particularly, the Food and Nutrition Department (DAN), is a participant institution at CESAM, contributing mainly to the Environmental Biology & Health (EB&H) thematic line and developing studies under the Stress Biology working group (SB WG). One of the research focus at DAN concerns the development of studies related to the toxic effects of multiple mycotoxins present in food and its impact on human health1, particularly, children´s health. MYCOMIX (https://www.youtube.com/watch?v=CsKaz3mt2J4&t=27s), a national project funded by FCT (2013-15, Portugal), studied the toxic effects of children exposure (under 3 years old) to multiple mycotoxins in infant foods. MYCOMIX revealed that children were, in fact, exposed to 22 combinations of two to seven mycotoxins through breakfast cereals consumption2. Performed for the first time, the cumulative risk assessment showed that aflatoxins, compounds classified by IARC as carcinogenic for humans, could constitute a potential health concern for children until 3 years old when considering the high percentiles (P90, P95 and P99) of consumption of breakfast cereals3. Face to these results and since cereal-based foods are important for the children´s diet, a Partnering Grant Project (GP/EFSA/AFSCO/2017/01-GA02), entitled “RiskBenefit4EU – partnering to strengthen the risk benefit assessment within EU using a holistic approach” is on course aiming to strengthen the EU capacity to access and integrate food risks and benefits in the areas of microbiology, nutrition and toxicology through the development of a harmonized framework that will be available to EU member states organizations4. Human biomonitoring has become an important tool in the evaluation of exposure to chemicals in the general population and specific subgroups. The determination of mycotoxin biomarkers in biological fluids is another strategy that DAN is recently developing, through a PhD thesis and participation in the European Human Biomonitoring Initiative (www.hbm4eu.eu), a H2020 funded project. Currently, climate change is an important issue and since it is closely related to food safety, DAN team reviewed and discussed the potential influence of climate change on the health risk associated to aflatoxins dietary exposure of Portuguese population5. The comprehensiveness of these topics implies multidisciplinary approaches, promoting the development of knowledge in the domains of food safety towards a healthier environment.